Typing and susceptibility to penicillin of Neisseria meningitidis isolated from patients in Cuba (1993-1999) - Jorge Sosa; Rafael Llanes; Daymi Guzmán; Ibrahín Quintana; Mayra Flores; Oderay Gutiérrez (Memorias do Instituto Oswaldo Cruz, 2001)
The susceptibility to penicillin of 111 Neisseria meningitidis strains was assessed by the agar-dilution procedure and serosubtypes were determined by a whole-cell enzyme-linked immunoassay using monoclonal antibodies reagents. Thirty-five isolates showed reduced sensitivity to penicillin (MIC > or = 0.1 mg/l and <= 1 mg/l) and no resistant strains were detected. The most common phenotype was B:4:P1.15 (77.5%) and a rising trend of non-typeable and non-subtypeable strains was detected. The increase in levels of minimal inhibitory concentrations of meningococci to penicillin gives cause for concern and the increase in non-typeable and non-subtypeable isolation demand the use of molecular biology techniques for their typing.